The impact of emotional support offered during rehabilitation on the long-term quality of life and satisfaction with living of individuals with spinal cord injury : an exploratory study of individuals re-employed in the South African National Defence Force - Parker, S. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Rehabilitation))--University of Stellenbosch, 2005.